The civil service structure and occupational status of school teachers in Bangladesh (1971-2001) - Quddus, S. M. Abdul (Tribhuvan University, Kathmandu, Nepal, 2016)
Bangladesh has the Westminster type of political system, where the prime minister is the main executive, leader of the house and advises the president. The civil service is the administrative arm of the government and has the responsibility to serve the people of the country (GoB, 1994: Art 21). However, the structure of Bangladesh Civil Service shows a rigid pattern of ranks which correspondence to occupational type hence financial benefit, privileges, honours and power. The horizontal classification of civil service is also based on number of other factors such as educational requirements, level of responsibility and so on. Civil servants in Bangladesh are categorized into four “Classes” among which higher level civil servants are recognized as Class I “gazetted officers”. Below them are three other classes namely Class II, Class III, and Class IV “employees” performing jobs of varied responsibility. But less privileges, honour, and rewards are attached to these three lower-level “classes”. It is to mention that higher skill or occupational expertise, autonomy or self-directing, exclusiveness etc are some essential attributes of members of professionalized occupation. Most importantly, occupational expertise that justifies privileges and higher status depend on the state and its policies i.e. how a state officially define and classify particular kinds of work in the national labour market (Freidson, 2001:128). This article explores the development of the vocational situation in a historical context of primary schoolteachers particularly related with their position in the civil service system in Bangladesh. This paper argues that primary schoolteachers’ position in the country’s civil service system in Bangladesh put them in an unfavourable situation to achieve qualities of members of a professionalized occupation.